Avian Predation at a Southern Rockhopper Penguin colony on Staten Island, Argentina - Liljesthrom, Marcela; Emslie, Steven Douglas; Dargan,Frierson.; Schiavini, Adrian Carlos Miguel (Polar Biology)
We studied predation risk in relation to nest location and subcolony size in Southern Rockhopper Penguins (Eudyptes chrysocome chrysocome) during the chick-rearing period. Striated Caracaras (Phalcoboenus australis), the main predator, preferentially attacked from tussock grasses which are found in the periphery of all subcolonies (peripheral tussocks) and often scattered within them (central tussocks). The greatest numbers of predation and attempted predation events were observed on nests in the periphery of the subcolony next to peripheral tussocks, and on those nests next to central tussocks. Central tussocks offer Striated Caracaras an additional "edge" area from which to prey, much in the same way as do the peripheral tussocks. Predation rate per individual was not correlated with subcolony size possibly due to the presence of central tussocks which, by creating an extra edge area, change the subcolony shape. There is a suggestion (P = 0.06) of increased probability of nest success with subcolony size. Fil: Liljesthrom, Marcela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. University of North Carolina; Estados Unidos Fil: Emslie, Steven Douglas. University of North Carolina; Estados Unidos Fil: Dargan,Frierson. University of North Carolina; Estados Unidos Fil: Schiavini, Adrian Carlos Miguel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina